ASSESSING THE READINESS OF FLEXIBLE WORKING SYSTEMS AND EMPLOYEE ENGAGEMENT : THE SIGNIFICANCE OF TRANSFORMATIONAL LEADERSHIP IN MILLENNIAL AND GENERATION Z AT THE DJKN SECRETARIAT - Setyoningtyas, Prinindia Rizky; Febriansyah, Hary (LPPM STIE Muhammadiah Bandung, 2024)
The need for bureaucratic reform, digital transformation, and the COVID-19 pandemic encourage the Ministry of Finance to implement a flexible working system in accordance with Minister of Finance Regulation (KMK) No. 416 of 2023. This study focuses on employees in the Secretariat of DJKN, particularly Millennials and Generation Z. This research employs mixed method that involves quantitative and qualitative aspects. The quantitative component used structured questionnaires to collect numerical data on the flexible working system, transformational leadership, and their impact on employee engagement. The qualitative component involved in-depth interviews with key organizational figures. Quantitative data analysis employed moderation regression analysis (MRA) to examine the relationship between the flexible working system and employee engagement, as well as how transformational leadership moderates this relationship. The research findings indicate that the flexible working system has a significantly positive impact on employee engagement, especially among Millennials and Generation Z. Additionally, transformational leadership significantly enhances the effectiveness of the flexible working system. Leaders who inspire and motivate their team members can amplify the positive effects of flexible work arrangements on employee engagement.